Strategi Pengelolaan Desa Wisata Penglipuran Kabupaten Bangli - I Nengah Arya Wibowo (Public Inspiration : Jurnal Administrasi Publik, 2019)
Abstract Penglipuran Tourism Village recently is popular as an alternative tourist destination, for the development of the tourism village it is needed appropriate management strategy for a better achievement in the future. Recently, Penglipuran tourism village managed by Penglipuran management tourism committee which is under responsibility of Penglipuran village. This research tried to figure out appropriate strategy to manage Penglipuran tourism village. Three issues being discussed were: (1) how was the strategy to manage Penglipuran tourism village, (2) the participation of Bangli regency government in managing Penglipuran tourism village, (3) the impact of Penglipuran tourism village management toward the community. The goal of this research were to know how the management of Penglipuran tourism village; to know the participation of the government of Bangli regency in managing Penglipuran tourism village ; and to know the positive and negative impact of Penglipuran tourism village management system which include economic, culture, environment, social and community. The approach being used in this research was descriptive qualitative method by applying the theory of Management Strategy (Paul Joyce), SWOT analysis (Freddy Rangkuti), Participation Theory (Leach, Stewart and Walsh), and the theory of Tourism Impact (Pitana and Gayatri). Data collection conducted through observation, interview and documentation. Informants were selected through purposive sampling technique and the data were analyzed through qualitative descriptive and SWOT analysis. The research showed that the appropriate strategy to manage Penglipuran tourism village were (SO, ST, WO, WT). The participation of Bangli regency government was still low due to the limited of budget, facilities and participation. In term of management impact was found that the existence of Penglipuran tourism village gave more advantages to the community whether in economic, culture, environment and also social side. Keywords: Management strategy; government participation; tourism management impact Abstrak Desa Wisata Penglipuran baru-baru ini populer sebagai tujuan wisata alternatif, untuk pengembangan desa wisata diperlukan strategi manajemen yang tepat untuk pencapaian yang lebih baik di masa depan. Baru-baru ini, desa wisata Penglipuran dikelola oleh komite pariwisata manajemen Penglipuran yang berada di bawah tanggung jawab desa Penglipuran. Penelitian ini mencoba mencari strategi yang tepat untuk mengelola desa wisata Penglipuran. Tiga isu yang dibahas adalah: (1) bagaimana strategi mengelola desa wisata Penglipuran, (2) partisipasi pemerintah kabupaten Bangli dalam mengelola desa wisata Penglipuran, (3) dampak pengelolaan desa wisata Penglipuran terhadap masyarakat. Tujuan penelitian ini adalah untuk mengetahui bagaimana pengelolaan desa wisata Penglipuran; untuk mengetahui partisipasi pemerintah Kabupaten Bangli dalam mengelola desa wisata Penglipuran; dan untuk mengetahui dampak positif dan negatif dari sistem pengelolaan desa wisata Penglipuran yang meliputi ekonomi, budaya, lingkungan, sosial dan masyarakat. Pendekatan yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif dengan menerapkan teori Strategi Manajemen (Paul Joyce), analisis SWOT (Freddy Rangkuti), Teori Partisipasi (Leach, Stewart dan Walsh), dan teori Dampak Pariwisata (Pitana dan Gayatri) ). Pengumpulan data dilakukan melalui observasi, wawancara dan dokumentasi. Informan dipilih melalui teknik purposive sampling dan data dianalisis melalui deskriptif kualitatif dan analisis SWOT. Penelitian menunjukkan bahwa strategi yang tepat untuk mengelola desa wisata Penglipuran adalah (SO, ST, WO, WT). Partisipasi pemerintah Kabupaten Bangli masih rendah karena keterbatasan anggaran, fasilitas dan partisipasi. Dari segi dampak manajemen ditemukan bahwa keberadaan desa wisata Penglipuran memberi lebih banyak keuntungan bagi masyarakat baik dari sisi ekonomi, budaya, lingkungan maupun sosial. Kata kunci: Strategi manajemen; partisipasi pemerintah; dampak pengelolaan pariwisata